The Significance of OCTA in Studying Vessel Density and Retinal Thickness in Individuals with Myopia - Marija Veselinović; Marija Trenkić; Vladimir Čanadanović; Predrag Jovanović; Aleksandar Veselinović; Maja Petrović; Aida Kasumović Bećirović (Medicina)
Background and Objectives: This study explores the relationship between retinal structure, vascular densities (VD), and the progression of myopia, aiming to identify novel biomarkers for assessing myopia severity. Materials and Methods: A total of 260 eyes were divided into four groups: Emmetropia (EM) (n = 74), Low Myopia (LM) (n = 68), Moderate Myopia (MM) (n = 64), and High Myopia (HM) (n = 54). VD and retinal thickness (RT) in the macular and peripheral quadrants were measured using optical coherence tomography-angiography (OCTA). SVD and DVD were analyzed across the paranasal, peritemporal, perisuperior, and peri-inferior quadrants. Results: Significant differences in superficial vessel density (SVD) were found in the paranasal (EM vs. MM, p = 0.017; EM vs. HM, p = 0.001), peritemporal (EM vs. MM, p = 0.006; EM vs. HM, p = 0.001; LM vs. HM, p = 0.004; MM vs. HM, p = 0.032), perisuperior (EM vs. MM, p = 0.005; EM vs. HM, p = 0.001; LM vs. HM, p = 0.027), and perifoveal quadrants (EM vs. MM, p = 0.003; EM vs. HM, p = 0.008; LM vs. HM, p = 0.004; MM vs. HM, p = 0.012). Deep vessel density (DVD) showed significant differences in the paranasal (p = 0.012–0.022), peritemporal (p = 0.002–0.026), perisuperior (p = 0.003–0.034), perifoveal (p = 0.002–0.017), and peri-inferior (p = 0.002–0.022) quadrants. Retinal thickness was significantly reduced in HM eyes, with the most pronounced reduction in the peritemporal quadrant (mean difference: 16.7 ± 3.2 µm; p < 0.001). Conclusions: Structural and vascular changes in the retina become more pronounced as myopia progresses from moderate to high. The strong correlation between DVD, RT, and myopia severity highlights their potential as reliable biomarkers for monitoring myopia progression through OCTA imaging. These findings provide new insights into the vascular and structural changes underlying myopia and their diagnostic significance.